First series of mechanical circulatory support in non-compaction cardiomyopathy: Is LVAD implantation a safe alternative?. (15th October 2015) - Uribarri, Aitor; Rojas, Sebastian V.; Avsar, Murat; Hanke, Jasmin S.; Napp, L. Christian; Berliner, Dominik; Bavendiek, Udo; Bauersachs, Johann; Bara, Christoph; Sanchez, Pedro L.; Haverich, Axel; Schmitto, Jan D.
Abstract: Background: Left ventricular non-compaction (LVNC) is a rare cardiac disorder characterized by prominent trabeculae and deep recesses of the ventricular myocardium. Patients with LVNC may develop severe congestive heart failure refractory to medical therapy. However, heart transplantation is strongly limited due to donor organ shortage. Thus mechanical circulatory support by left ventricular assist devices (LVADs) is a promising alternative. Nevertheless, hypertrabeculation and proarrhythmogenic potential in LVNC might represent important hurdles for success of LVAD therapy in these patients. Methods and results: We retrospectively analyzed the data of a total of 5 patients (3 HVAD, Heartware®; 2 HeartMate II, Thoratec®) with LVNC who underwent LVAD implantation in our institution between 2010 and 2014. Mean follow-up time was 86.5 weeks. 30-day survival was 100% without major intrahospital complications. During follow-up, 3 patients developed pump thrombosis requiring pump replacement. Arrhythmias were not detected during follow-up as assessed by ICD interrogation. Conclusions: LVAD implantation in LVNC can be performed with low intrahospital complication rates. However, we observed a high incidence of pump thrombosis during follow-up, possibly related to thromboembolic predisposition by the underlying LVNC. Therefore, careful management of anticoagulation appears to be critical in these patients.